2009
DOI: 10.1172/jci32661
|View full text |Cite
|
Sign up to set email alerts
|

Maternal high-fat diet triggers lipotoxicity in the fetal livers of nonhuman primates

Abstract: Maternal obesity is thought to increase the offspring's risk of juvenile obesity and metabolic diseases; however, the mechanism(s) whereby excess maternal nutrition affects fetal development remain poorly understood. Here, we investigated in nonhuman primates the effect of chronic high-fat diet (HFD) on the development of fetal metabolic systems. We found that fetal offspring from both lean and obese mothers chronically consuming a HFD had a 3-fold increase in liver triglycerides (TGs). In addition, fetal offs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

46
562
10
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 420 publications
(641 citation statements)
references
References 98 publications
46
562
10
6
Order By: Relevance
“…This has been associated with altered hepatic mitochondrial electron transport chain complex activity and with increased expression of genes involved in lipogenesis, oxidative stress and inflammation (Bruce et al 2009). An effect of maternal high-fat diet on offspring liver triglyceride content has also been shown in non-human primates in which the offspring of females maintained long-term on a high-fat diet had increased liver triglyceride content and evidence of increased hepatic oxidative stress whether or not their mothers had become obese, suggesting that programming of liver fat may be independent of maternal obesity, at least in this model (McCurdy et al 2009). The impact of maternal obesity in humans on offspring development of non-alcoholic fatty liver disease has not been studied, although preliminary evidence suggests that early feeding habits may impact on development of fatty liver disease in childhood suggesting a potential role for early life experience in development of this condition (Nobili et al 2009).…”
Section: Non-alcoholic Fatty Liver Diseasementioning
confidence: 56%
“…This has been associated with altered hepatic mitochondrial electron transport chain complex activity and with increased expression of genes involved in lipogenesis, oxidative stress and inflammation (Bruce et al 2009). An effect of maternal high-fat diet on offspring liver triglyceride content has also been shown in non-human primates in which the offspring of females maintained long-term on a high-fat diet had increased liver triglyceride content and evidence of increased hepatic oxidative stress whether or not their mothers had become obese, suggesting that programming of liver fat may be independent of maternal obesity, at least in this model (McCurdy et al 2009). The impact of maternal obesity in humans on offspring development of non-alcoholic fatty liver disease has not been studied, although preliminary evidence suggests that early feeding habits may impact on development of fatty liver disease in childhood suggesting a potential role for early life experience in development of this condition (Nobili et al 2009).…”
Section: Non-alcoholic Fatty Liver Diseasementioning
confidence: 56%
“…High fat consumption during pregnancy induces features of MetS including dyslipidaemia in adult offspring, independent of adult environmental factors (12)(13)(14) . A maternal high-fat diet (HFD) in nonhuman primates triggers lipid accumulation, inflammation and oxidative stress in the fetal liver (15) . These data indicate that the developing fetus is highly vulnerable to excess lipids.…”
Section: Developmental Origin Of Adult Health and Diseasementioning
confidence: 99%
“…The impact of early in life high fat diet exposure are noteworthy and include non-alcoholic fatty liver disease (NAFLD) with lipid accumulation, pancreatic and immune modulatory dysfunction, thyroid hormone dysregulation, hypertension, and alterations in sirtuins and their regulated pathways 18,27,[50][51][52] . These further manifest as aberrant metabolic homeostasis and altered behaviors at both 1 and 3 years of age 30,31 , with early increased body mass trajectories.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, we have spent nearly a decade establishing and characterizing the effect of obesity and chronic high fat dietary exposure on adult female dams and their offspring in Macaca fuscata (Japanese macaque) [18][19][20][21] . Specifically, we have demonstrated that a high fat diet (HFD) comprised of 36% calories from fat during gestation and lactation structures the offspring's epigenome, metabolome, and intestinal microbiome 18,19,[22][23][24][25][26][27] ; these molecular and metabolic perturbations are accompanied by persistent changes in offspring behavior and impairments in critical neural circuitry despite weaning to a healthy diet 28 . Of interest, we have consistently observed that HFD feeding for 1-5 years prior to pregnancy leads to insulin resistance and obesity in the majority, but not all, exposed dams 18,23,26,27,[29][30][31] .…”
mentioning
confidence: 99%